2019
DOI: 10.1177/1758835919855491
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CSPG4 as a promising target for translational combinatorial approaches in osteosarcoma

Abstract: Background: Osteosarcoma (OSA) is a highly metastatic pediatric bone tumor. Adjuvant chemotherapy and surgical resection represent standard treatments; however, the prognosis is still poor. Effective strategies are urgently needed. Chondroitin sulfate proteoglycan (CSPG)4 is a transmembrane proteoglycan with a low expression in normal tissues but high expression in several solid tumors, where it plays a central tumorigenic role. Therefore, it represents a promising therapeutic target. The high hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
(133 reference statements)
1
26
0
Order By: Relevance
“…CSPG4 is a promising target antigen highly expressed in multiple tumor types, including melanoma, glioblastoma, breast carcinomas, osteosarcoma and hematologic cancers. 25,35 Originally believed to have a very limited distribution in normal adult tissues, 36 CSPG4 expression has since been observed Figure 3. Molecular analysis of immediate effects of in vivo α-CSPG4 rIgE administration.…”
Section: Discussionmentioning
confidence: 99%
“…CSPG4 is a promising target antigen highly expressed in multiple tumor types, including melanoma, glioblastoma, breast carcinomas, osteosarcoma and hematologic cancers. 25,35 Originally believed to have a very limited distribution in normal adult tissues, 36 CSPG4 expression has since been observed Figure 3. Molecular analysis of immediate effects of in vivo α-CSPG4 rIgE administration.…”
Section: Discussionmentioning
confidence: 99%
“…GET of human CSPG4 (hCSPG4) has also been shown to be safe and effective in the treatment of dogs with spontaneous OMM ( 70 , 71 ); the human sequence of CSPG4 was intentionally used in these studies due to its high homology and similarity to canine CSPG4 and demonstrated ability to induce a specific humoral response against the human and canine protein, which is related to the successful outcome of the treatment ( 68 ). CSPG4 immune targeting also appears to be a promising treatment modality for appendicular OSA in dogs, as documented in an in vitro model ( 69 ).…”
Section: Basic Principles Of Electroporation-based Treatments and Genmentioning
confidence: 99%
“…As CSPG4 displays low expression levels on healthy adult (human and canine) cells and is expressed on the cell surface (Class 1 oncoantigen), it is an ideal target for effective anti-cancer immunotherapy in dogs and humans. A canine model appears to be very useful in translational studies, as CSPG4 expression was found in canine malignant melanoma and osteosarcoma (OSA) ( 68 , 69 ) and has been related to significantly shorter survival in dogs with appendicular OSA ( 69 ). GET of human CSPG4 (hCSPG4) has also been shown to be safe and effective in the treatment of dogs with spontaneous OMM ( 70 , 71 ); the human sequence of CSPG4 was intentionally used in these studies due to its high homology and similarity to canine CSPG4 and demonstrated ability to induce a specific humoral response against the human and canine protein, which is related to the successful outcome of the treatment ( 68 ).…”
Section: Basic Principles Of Electroporation-based Treatments and Genmentioning
confidence: 99%
“…To measure cell migrative ability [ 54 ], 2 × 10 4 MDA-MB-231 and 4T1 cells were seeded in the top chamber of a 24-transwell plate (8 μm pore size; Corning, Amsterdam, The Netherlands) after 1 h of pre-incubation with 1:50 dilutions of pooled sera from mice vaccinated with AX09 or MS2 wt or left untreated in a serum-free medium. Then, the bottom chambers of the transwell plates were filled with 600 μL of complete growth medium and the cells were incubated at 37 °C in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%